A Systematic Literature Review of Organizational Performance through Talent Management Strategies - Yuliana, Rena; Senen, Syamsul Hadi (Westscience Press, 2023)
This research aims to deeply and thoroughly analyze various talent management strategies that have been proposed and implemented in the related literature. The research method used is Systematic Literature Review (SLR) by following the PRISMA stages to collect, review, and synthesize key findings related to optimizing organizational performance through talent management strategies over the past five years (2018-2023). This research will focus on identifying strategies that have proven successful in creating a work environment that supports the development and optimal utilization of employee potential. By involving concepts such as recruitment, employee development, retention, and overall talent management, this research aims to provide a holistic view of how organizations can integrate talent management strategies to achieve optimal performance goals. The results of this study are expected to provide valuable insights for business practitioners, HR managers, and researchers in the development and implementation of effective talent management strategies. In addition, this research can serve as a foundation for the development of conceptual models that can be adapted by organizations in the face of changing market dynamics and competition.